Effect of Colchicine-Resistant Familial Mediterranean Fever on Growth Parameters - Betül SÖZERİ,; Ebru YILMAZ,; Sevgi MİR,; Afig BERDELİ, (Archives of Rheumatology, 2011)
Objectives: This study aims to evaluate the growth and development in patients with Familial Mediterranean fever (FMF) resistant to colchicine treatment. Patients and methods: Eighty-seven patients (45 females, 42 males; mean age 9.6±3.8 years; range 2 to 17 years) diagnosed with FMF according to Tel Hashomer criteria in the Pediatric Nephrology Department of Ege University Faculty of Medicine were included in the study. All patients had leukocytosis and elevated C-reactive protein, fibrinojen levels, erythrocyte sedimentation rate and serum amyloid A levels during attacks. The patients were divided into two groups according to colchicine treatment response. Twenty-seven patients (13 girls, 14 boys; mean age; 9.9±3.2 years) having frequent attacks (>1 attact/3 month) despite receiving 2 mg/day colchicine treatment were defined as colchicine-resistant. Sixty patients were defined as colchicine treatment responders. Anthropometric evaluations of the patients were performed at diagnosis and at the end of the follow-up. The height and weight Z scores of patients were used as growth parameters. Results: No statistically significant difference in mutation frequency was found between the groups. There were no significant differences between both groups in the weight and height Z scores calculated from the anthropometric parameters detected at the diagnosis. In the evaluation performed at the end of the follow-up, we found that the height and weight score for age and the body mass index Z score were significantly decreased in the colchicine resistance group (p=0.008, p=0.013, p=0.027). Conclusion: Effective suppression of inflammatory response in patients with FMF provides a positive impact on growth. While colchicine is known as the most effective drug in the treatment of FMF, it is known that there are also patients who fail to respond adequately. The patients with colchicine-resistant FMF should be identified in the early period of the disease and treatment should be arranged accordingly. The detection of growth retardation was found to be important in detecting resistance to colchicine in patients with FMF.